2013
DOI: 10.3390/nu5083163
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities and Bioavailability of Mangosteen Xanthones: A Critical Review of the Current Evidence

Abstract: Mangosteen (Garcinia mangostana L.) is a tropical tree native to Southeast Asia that produces a fruit whose pericarp contains a family of tricyclic isoprenylated polyphenols referred to as xanthones. Numerous in vitro studies have shown that these xanthones possess anti-oxidant, anti-proliferative, pro-apoptotic, anti-inflammatory and anti-carcinogenic activities. Aggressive marketing of such health promoting benefits has resulted in mangosteen’s classification as a “superfruit”. This has led to sales of mango… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
145
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(147 citation statements)
references
References 56 publications
0
145
0
2
Order By: Relevance
“…GML possess phytochemicals like xanthones, phenols and other flavonoids, which have been shown to be effective in scavenging free radicals. 39,40 Therefore by acting as an alternate radical scavenger, GML can replenish these antioxidant enzymes, thereby preventing oxidative stress. These results of our investigations are in accordance with that of Weecharangsan et al, 41 who have reported the antioxidant activity of GML pericarp extract.…”
Section: Discussionmentioning
confidence: 99%
“…GML possess phytochemicals like xanthones, phenols and other flavonoids, which have been shown to be effective in scavenging free radicals. 39,40 Therefore by acting as an alternate radical scavenger, GML can replenish these antioxidant enzymes, thereby preventing oxidative stress. These results of our investigations are in accordance with that of Weecharangsan et al, 41 who have reported the antioxidant activity of GML pericarp extract.…”
Section: Discussionmentioning
confidence: 99%
“…Suplemen berbahan dasar ekstrak kulit manggis (Garcinia mangostana L.) diketahui mengandung zat aktif xantone dengan konsentrasi yang tinggi yang terbukti memiliki efek antiin amasi yang kuat. 11 Berdasarkan latar belakang di atas, penelitian ini bertujuan untuk mengetahui pengaruh konsumsi suplemen ekstrak kulit manggis (Garcinia mangostana L.) terhadap in amasi gingiva pada pasien ortodonti cekat dengan kajian jumlah leukosit pada cairan sulkus gingiva.…”
Section: Pendahuluanunclassified
“…The xanthones, α-and γ-mangostin, are major bioactive compounds found in fruit hulls of the mangostin [18]. α-mangostin has some pharmacological activities such as antioxidant [19], anti-TB [16,19], MTB-MDR [19,20], anti-inflammatory activities [21], pro-inflammatory activities [18], and increased the permeability of the bacterial cell membrane [22][23][24]. The compound α-mangostin is expected to contribute to the fight against and eliminate TB infection and MTB-MDR [16,19].…”
Section: Stimulation Of Antigen Mtb Will Response T-cells T-cell Cd4mentioning
confidence: 99%